Seroprevalence of SARS-CoV-2 in domestic canines and felines from the city of Villavicencio, Colombia (Orinoquia, 2021)
Objective: To determine the seroprevalence of anti-SARS-CoV-2 immunoglobulins (Ig) type G (IgG) in domestic dogs and cats, and their epidemiological association with positive COVID-19 RTq-PCR cases in the communes of the city of Villavicencio, Colombia. Methodology: An observational, analytical and cross-sectional study was carried out, in which antiSARS-CoV-2 IgG was measured in blood serum by indirect ELISA in a representative and random sample (n = 435) of felines (135) and canines(300) domestic in Villavicencio (N = 68,651). The Odds Ratio (OR) (p
Keywords: pandemic; zoonoses; intermediate hosts; severe acute respiratory syndrome due to coronavirus 2 (SARSCoV- 2); coronavirus disease 2019 (COVID-19)